Baitul Rahmah: a final evolution of the Malay classical style amidst change - Abdul Majid, Noor Hanita; Jahn Kassim, Puteri Shireen; Raja Abdul Kadir, Tengku Anis Qarihah; Sapian, Abdul Razak; Samsuddin, Abu Dzar (Universitas Indraprasta PGRI, 2020)
The paper highlights the significance and position of the Baitul Rahmah, an early 20th-century mansion in Kuala Kangsar, Perak, Malaysia, as a key milestone of stylistic evolvement of local vernacular architecture. Its form embodies, a typological variation at a time of growing Colonial imperialism, while its grammar and language refers to early modern stylistic expression reflecting the fundamental principles of indigenous architecture. The Baitul Rahmah brings to light how a final evolution and epitome of the vernacular projects an identity as a cosmopolitan manifestation. Its internal ornamentation recalls the stylized forms of local motifs and reflect a form of control and minimalism; i.e. an ‘ornamental decorum’. Its wood-carved expressions seem stylised into increasing ‘modernised’ simplication and modularity, while its masonry- timber structure reflect the identity of hybridity in architecture which symbolise the tensions of local communities as they step into the 1900s into a global context.